STUDI LITERATURE: TANAMAN OBAT YANG MEMILIKI POTENSI PENYEMBUHAN UNTUK LUKA TERBUKA YANG TERJADI PADA ANAK - Oashttamadea, Ressa; Sabil, Ukhti Khaula (AKADEMI PEREKAM DAN INFORMASI KESEHATAN (APIKES) IRIS PADANG, 2024)
The process of a wound occurs, namely that blood will come out through the wound, then blood platelets touch the surface of the wound and then release thrombokinase, assisted by calcium ions, which will convert prothrombin into thrombin. Aim of this research to find out the benefits of medicinal plants that have the potential to heal open wounds that often occur in children, and aims to reveal and convey the types/species of plants used in treating open wounds. Method article review by searching several national and international journal publications via the database: Google Scholar. The keywords used are